Atrial natriuretic peptide and blood volume during red cell transfusion in preterm infants. Issue 4 (April 1991) - Rascher, W; Lingens, N; Bald, M; Linderkamp, O
Abstract : Because raised plasma concentrations of atrial natriuretic peptide indicate volume expansion, we studied the effect of red cell transfusion on plasma atrial natriuretic peptide concentration, packed cell volume, and intravascular volume in eight preterm infants. Red cell transfusion increased red cell mass, packed cell volume and erythrocyte count, but decreased plasma volume. Total blood volume, plasma atrial natriuretic peptide concentration, urine flow rate, and urinary sodium excretion did not change. We conclude that a slow transfusion of less than 10 ml red cells/kg body weight does not cause volume expansion with subsequent atrial natriuretic peptide release thereby affecting the cardiovascular system.